Implementation of the Mobsi Mobile Presence System in Improving the Discipline of State Civil Apparatus - Ervina, Ervina; Widiyanti, Sri; Wijaya, Junior Hendri (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Public sector organizations increasingly adopt e-government solutions to enhance administrative efficiency and employee discipline, particularly in attendance management systems. Specific Background: The Gunungkidul Regency Government replaced a manual attendance system—prone to manipulation, errors, and delayed reporting—with the MOBSI mobile presence system to improve discipline among State Civil Apparatus (ASN). Knowledge Gap: Despite growing adoption of mobile attendance systems, empirical evidence on their effectiveness in strengthening discipline and supervision in local government institutions remains limited. Aims: This study aims to analyze the implementation of the MOBSI mobile presence system and its role in improving ASN discipline in Gunungkidul Regency. Results: Using a qualitative case study approach involving key officials of the Pamong Praja Police Unit, the findings indicate that MOBSI enables real-time, GPS-based attendance monitoring, enhances supervisory control, simplifies data recording, and contributes to consistently high attendance rates throughout 2024. Novelty: This study provides contextual evidence of how a geolocation-based mobile attendance system functions as both a technological and managerial instrument for discipline enforcement in local government. Implications: The findings suggest that integrating mobile attendance systems within e-government frameworks can strengthen accountability, improve work discipline, and ultimately enhance the quality of public services in regional governments. Highlights: Digital Attendance Innovation: MOBSI replaces manual attendance with a GPS-based mobile system to ensure accurate and real-time monitoring. Discipline and Accountability: The system strengthens ASN discipline by reducing manipulation and improving supervisory control. E-Government Impact: MOBSI supports administrative efficiency and enhances the quality of public services in local government. Keywords: Mobile Attendance System, ASN Discipline, E-Government, GPS-Based Monitoring, Public Service Performance